Comment: On the nature of "unconventional twins" in magnesium. (February 2023) - Lin, F.X.; Wu, C.C.; Fang, X.Y.; Liu, H.; Nie, J.F.
Abstract: "Unconventional twins" were reported by Cayron and Logé [1] to form in plastically deformed magnesium. They were used to show the occurrence of a new twinning mode which was used to argue for reconsidering the theory of deformation twinning that is based on simple shear [1], and to support a concept of axial weak twins [2]. Our paper demonstrates the incorrect interpretation of their electron back-scatter diffraction map in [1], and that the so-called "unconventional" twins are just conventional extension twins that have impinged with each other. Therefore, the so-called habit plane of the "unconventional twins" is a boundary resulting from impingement of these two different variants of the extension twin, and is therefore not expected to be invariant.